A study on factors affecting emloyee motivation at Jabatan Kesihatan Negeri Perlis / Nor Hidayah Abd Rahman - Abd Rahman, Nor Hidayah (2014)
Employee motivation is important in organization as a force that drives the employees toward attaining objectives and goal of organization. The current era is highly competitive and organizations regardless of size, technology and market focus are facing employee motivation challenges. Purpose of this study basically to identify what kind of factors that affecting employee motivation in a Jabatan Kesihatan Negeri Perlis. The data were collected from employees of different departments in Jabatan Kesihatan Negeri Perlis. In all 125 set of questionnaires were distributed among the employees of different departments and they returned 103 completed useable questionnaires for response rate of 82%. The participation in survey was voluntary and confidentiality of responses was ensured. The statistical analysis showed that from five independent variable only two independent variable that significant to dependent variable, employee motivation which are training and development and organization culture.